The Impact of "Brand-Place-Painter" in Growth and Development of Gallery Browsing - Emami, Nooshin; Hamidi, Naser (Journal of History Culture and Art Research, 2017)
This research investigates effect of "brand - place - painter" in growth and development of gallery browsing as well as what extent can have an impact on selection of visitors to choose a painting exhibition (gallery). Components that have been evaluated are brand loyalty, observed quality, brand image and brand values. The study seeks answer to which one has highest and lowest impact as been a tourist destination. For this purpose, painting exhibitions in Cultural Center in Tehran have been observed during two months, September and October of 2016. 384 questionnaires have been collected to carry the research. The results suggest that among the components that have been studied, brand value have had highest impact (40%) on brand equity and brand loyalty have had the least impact (12%) on brand equity.